Pengaruh Profitabilitas, Leverage, Likuiditas Dan Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sub Sektor Apparel & Luxury Goods Yang Terdaftar Di Bursa Efek Indonesia - Soraya, Hasna; Ramayani, Citra; Dahen, Lovelly Dwinda (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2026)
This study aims to determine the profitability, leverage, liquidity and capital structure on the company value of manufacturing companies in the apparel and luxury goods sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. This type of research is associative research. Associative research is research that tests whether there is a relationship or influence between one variable and another. This research is included in associative research because it aims to determine the analysis of the impact of profitability, leverage, liquidity, capital structure on the company value of manufacturing companies in the apparel and luxury goods sub-sector listed on the Indonesia Stock Exchange between independent variables and dependent variables. The results of this study indicate that profitability, leverage, liquidity and capital structure simultaneously have a significant effect on the company value of companies in the apparel and luxury goods sub-sector.